Pembuatan Logo, Peningkatan Marketing Online Inovation, Dan Pembukuan Sederhana Pada Usaha Mikro Kecil Menengah Di Toko Kelontong Vian Cell Kelurahan Kejuron Kecamatan Taman Kota Madiun - Fauzi, Rizal Ula Ananta; Kadi, Dian Citaningtyas Ari; Ningrum, Isabela Indah Puspita; Marisa, Pascawati Ida; Anggraida, Riska Winiayu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2022)
Micro, Small and Medium Enterprises (MSMEs) are independent businesses, with certain assets and excluding land and buildings. People's economic activities are small-scale and need to be protected to prevent unfair competition between other businesses. This community service, we discussed about a grocery store that has the potential to be developed in the future. This business has been running since 2013 namely Vian Cell Grocery Store. The problems that exist in this business include labeling goods, online marketing, and not having books to find out profit or loss every month. Following up on existing problems, we have a work program to create a logo which will later be in the form of stamps and stickers. We are also expanding the market share of this store by becoming a Gojek application partner. Our last work program is to provide socialization in the form of the importance of using simple bookkeeping and teach about simple bookkeeping that can be used to improve the quality of this store.